Pengaruh Social Media Marketing dan Kualitas Produk terhadap Keputusan Pembelian Kain Tenun di Sanggar Bliran Sina Watublapi Desa Kajowair, Kecamatan Hewokloang, Kabupaten Sikka - Antonius Charlos; Walter Obon; Nunsio H. Meylano (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This reserch aimed to analyze the effect of social media marketing and product quality one the purchhasing for Woven Fabric at Sanggar Bliran Sina. This research method was used quantitatively by involing 108 respondents, who were consumers of sanggar Bliran Sina. The sample was selected using purposive sampling method and data colllection was carried out throught filling out a questionnaire. Data analysis was done throught Multipple Linear Regresskion using 26 for Windowa softwere. The result showed that the social media marketing variable (X1) had no significan effect one the purchasing decision variable(Y). In contrash, the product quality variable partial the product quality varible (X2) had a subtantial effect one the purchasing decision variable (Y). The results of statistical tests based on Anova calculations showed that the F-count value of 66.332 with a significance value of 0.000. It can be concluded that the 2 independent variables, namely the social media marketing variable (X1) and product quality (X2) had a significant effect on purchasing decisions (Y).